(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Electricity is the set of physical phenomena associated with the presence and flow of electric charge. Electrical injuries are a relatively common type of mechanical trauma that can be caused by lightning, low-voltage trauma, or high-voltage trauma. They frequently have high morbidity and mortality rates. A hospital based descriptive observational study that was conducted at the SMS Medical College, in the department of forensic medicine in Jaipur, Rajasthan from 20th June 2021 to 19th June 2022. There were 75 death cases from electrocution that were included in the sample. Males made up 92% of cases, while females made up only 8% of cases, for a male to female ratio of 11.5 to 1. The majority of the subjects (34.67%) are between the ages of 21 and 30. Age group 31–40 (26.67%) came next. There are 54 (72% of the total) rural residents in the area where the subject resides. The majority of the subjects, or 39 (52%), fell into the lower middle class according to the Modified Kuppuswamy scale. Mortality rate in fatal electrocution cases can be reduced by providing immediate and adequate resuscitation. Although accidental electrocution accounts for the majority of fatalities, suicidal and homicidal electrocution should also be taken into account. In each of these situations, the incident’s history, along with a thorough investigation of the crime scene and an autopsy report may enable us to determine the death’s cause and manner, allowing us to use the information to plan and put into action preventive measures to lower the likelihood of future occurrences.